PENGGUNAAN FLASHCARD EMOJI DALAM MENINGKATKAN KECERDASAN INTERPERSONAL PADA ANAK TK A SARTIASARI SURABAYA - Eny Ariyanti (MOTORIC, 2020)
This research aims to improve children's interpersonal intelligence group A Kindergarten school year Sartiasari 2018-2019 by using a flashcard learning emoji. This research is a Research Action Class (PTK) conducted two cycles. The subject in this study A group of Kindergaten children Sartiasari Surabaya with age 4-5 years totalling 28 children. The object in this study was interpersonal intelligence. Data collection techniques in the study by observation and documentation. Research instrument used observation and guidance on analysis in quantitative descriptive. The results showed the ability of interpersonal intelligence of children can be improved through learning flashcard emoji. Kids are invited to know the range of expression flashcard emoji, emoji range expressions mimicked the flashcard, classify and guess her friend's expression with a flashcard emoji. The ability to know the range of expression on pre cycle reached 35.6%, then in the cycle I completeness average percentage of learning increased to 46.42% and the average percentage of completeness study on cycle II increased to 85.71%. Improvement of pre cycle to cycle I of 10.82%, and an increase from cycle I to cycle II amounted to 39.29%. Key words: interpersonal intelligence, flashcard emoji, kindergarten